2006
DOI: 10.1172/jci25426
|View full text |Cite
|
Sign up to set email alerts
|

Anaphylactic shock depends on PI3K and eNOS-derived NO

Abstract: Anaphylactic shock is a sudden, life-threatening allergic reaction associated with severe hypotension. Platelet-activating factor (PAF) is implicated in the cardiovascular dysfunctions occurring in various shock syndromes, including anaphylaxis. Excessive production of the vasodilator NO causes inflammatory hypotension and shock, and it is generally accepted that transcriptionally regulated inducible iNOS is responsible for this. Nevertheless, the contribution of NO to PAF-induced shock or anaphylactic shock i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
118
2
3

Year Published

2009
2009
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 123 publications
(133 citation statements)
references
References 55 publications
(87 reference statements)
10
118
2
3
Order By: Relevance
“…[22][23][24] Moreover, acute hypotension and lethality after antigen challenge and PAF injection entirely depend on the PI3K/Akt/eNOS pathway. 26 Our results also showed that inhibition of eNOS action by genetic or pharmacological manipulation in S1pr2 -/-mice markedly improved vascular leakage, hypotension and survival rate after antigen challenge, thus abrogating the effects of S1pr2 deficiency (Fig 3 and Fig E5). All these observations together indicate that S1P 2 provides a protective effect against vascular barrier disruption largely by suppressing eNOS.…”
Section: Discussionsupporting
confidence: 70%
See 2 more Smart Citations
“…[22][23][24] Moreover, acute hypotension and lethality after antigen challenge and PAF injection entirely depend on the PI3K/Akt/eNOS pathway. 26 Our results also showed that inhibition of eNOS action by genetic or pharmacological manipulation in S1pr2 -/-mice markedly improved vascular leakage, hypotension and survival rate after antigen challenge, thus abrogating the effects of S1pr2 deficiency (Fig 3 and Fig E5). All these observations together indicate that S1P 2 provides a protective effect against vascular barrier disruption largely by suppressing eNOS.…”
Section: Discussionsupporting
confidence: 70%
“…32 However, the previous study 26 showed that a specific inhibitor of soluble guanylate cyclase or genetic deletion of soluble guanylate cyclase-α1, a major isoform in the vasculature, did not protect mice from PAF-induced lethality, suggesting that NO might mediate shock in a manner independent of cGMP. In addition to guanylate cyclase-cGMP, NO may affect biological processes through causing S-nitrosylation of proteins.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent experiment with mice triggered anaphylactic shock by exposing the mice to an injection containing aluminum hydroxide and pertussis toxin [74]. This resulted in the excess synthesis of NO by eNOS, and a subsequent signaling cascade, mediated by the phosphatidyl inositol-3 kinase (PI3K) pathway.…”
Section: Mechanisms Of Aluminum and Mercury Toxicitymentioning
confidence: 99%
“…Agonists activate eNOS through multiple mechanisms: phosphorylation/ dephosphorylation of specific residues, interaction with different proteins, S-nitrosylation, and specific subcellular localization (1,(3)(4)(5)(6)(7). Agonists such as platelet-activating factor (PAF) and VEGF phosphorylate eNOS via Akt (8,9). Despite advances in our understanding of the biochemistry of eNOS, the mechanisms by which these molecular modifications determine the functional outcome of eNOS activation remain unexplored.…”
mentioning
confidence: 99%